Synergistic effects of multi-enzyme supplementation on nutrient digestion and absorption in the foregut and hindgut - Chen, Fangyuan; Zhao, Lianpeng; Huang, Lingjie; Zhuo, Yong; Xu, Shengyu; Lin, Yan; Che, Lianqiang; Feng, Bin; Wu, De; Fang, Zhengfeng (Frontiers in Veterinary Science, 2025)
This study was conducted to investigate the effect of dietary multi-enzyme (MCPC) supplementation on synergistically enhancing the functions of both the foregut and hindgut, ultimately improving the nutrient digestion and utilization throughout the gastrointestinal tract. In vitro results demonstrated that MCPC increased the phosphorus and reducing sugar levels in the supernatant during enzymatic hydrolysis. Furthermore, during the fermentation of the enzymatic hydrolysis products, MCPC significantly increased the FRD0 value of the enzymatic hydrolysis products from both the positive control (PC) and negative control 1 (NC1) diets (p < 0.05). MCPC reduced the T1/2 value of in vitro fermentation products from the PC diet (p < 0.01), and decreased the VF (p = 0.082) and K (p < 0.05) values for the NC1 diet. Additionally, 72 crossbred barrows [Duroc × (Landrace × Yorkshire)], weighing 25 kg, were fed one of six diets until their live weight approached 50 kg. The basal diets consisted of PC, NC1 and negative control 2 (NC2), while the remaining three diets were prepared by adding 100 mg/kg MCPC to the respective basal diets. The results showed that MCPC supplementation significantly upregulated the expression of solute carrier family 17 member 4 (SLC17A4) and vitamin D receptor (VDR) genes in the duodenum (p < 0.05), while downregulating the expression of Calbindin-D28k (CaBP-D28K) and solute carrier family 1 member 4 (SLC1A4) genes (p < 0.05) in growing pigs. Moreover, MCPC supplementation significantly upregulated the expression of VDR, glucose transporter 2 (GLUT2) and intestinal fatty acid binding protein (FABP2) genes in the jejunum of growing pigs. Furthermore, MCPC supplementation significantly increased the relative abundances of Bacteroidota, Prevotella and Phascolarctobacterium (p < 0.05), while reducing the relative abundances of Verrucomicrobiota and Clostridium_sensu_stricto_1 (p < 0.05) in the colon of growing pigs. In conclusion, MCPC enhances nutrient digestion and absorption in the foregut, provides fermentable substrates for hindgut microbial fermentation, and improves gut microbiota composition. This improves hindgut fermentation and supports the synergistic interaction between the foregut and hindgut, ultimately improving nutrient utilization and benefiting animal health.